Jogo de damas : um estudo sobre a influência das disposições de gênero da dança de salão na edificação do habitus - Dickow, Katiusca Marusa Cunha (2022)
This thesis aimed to investigate the construction of the habitus in ballroom dancing agents, based on the incorporation of gender dispositions maintained by the teaching processes of this social subfield, based on Pierre Bourdieu's theoretical premises. To conduct this investigation, the chosen location was the city of Porto Alegre, in the State of Rio Grande do Sul, as it is where the researcher works as a ballroom dance teacher. The main purpose of this investigation was to analyze the effects of reproducing and maintaining binary gender dispositions in ballroom dancing through the ballroom dance teaching processes, and to understand how these dispositions, which have been naturalized into this subfield agents' bodies and discourses, contribute to build the habitus of such agents. Our specific purpose was to study the social structures and the historical-cultural transformations that have been passing through the processes of body conformation and the formation of habitus, considering the founding dispositions of the field of ballroom dancing, analyzing how the gender dispositions are incorporated by the agents during their journey, as well as perceiving how the teaching processes operate in the construction and maintenance of these dispositions. For this analysis, Pierre Bourdieu's theoretical approaches to the concepts of capital, field and habitus were considered, as well as other authors who dialogue and discuss with Pierre Bourdieu’s assumptions. To build the data, an online questionnaire was developed containing 10 closedended and 8 open-ended questions. It was provided through a Google Forms form, aiming at ballroom dance teachers from Porto Alegre who had at least two years of professional experience in this field and at the students of these teachers. Of the 88 teachers invited to participate in the research, 46 responded to the questionnaire, as well as 43 students. Subsequently, from the responses to the questionnaires, semi-structured interviews were conducted with 8 teachers and 8 students, from September 2020 to May 2021. The results indicate that the agents have embodied the gender dispositions in their gestures and speeches, and that these dispositions were built through the teaching processes in which they participated. These dispositions build the habitus in a different way in each agent, and this building acts and moves within the social subfield of ballroom dancing, causing its binary and heteronormative structures to be questioned, displacing, even if in a restricted way, the modus operandi of this social subfield. This leads to a reflection on how these structures were built and why they continue to operate.